Freshening of Antarctic Intermediate Water in the South Atlantic Ocean in 2005–2014 - W. Yao (Ocean Science, 2017)
Basin-scale freshening of Antarctic Intermediate Water (AAIW) is reported to have occurred in the South Atlantic Ocean during the period from 2005 to 2014, as shown by the gridded monthly means of the Array for Real-time Geostrophic Oceanography (Argo) data. This phenomenon was also revealed by two repeated transects along a section at 30° S, performed during the World Ocean Circulation Experiment Hydrographic Program. Freshening of the AAIW was compensated for by a salinity increase of thermocline water, indicating a hydrological cycle intensification. This was supported by the precipitation-minus-evaporation change in the Southern Hemisphere from 2000 to 2014. Freshwater input from atmosphere to ocean surface increased in the subpolar high-precipitation region and vice versa in the subtropical high-evaporation region. Against the background of hydrological cycle changes, a decrease in the transport of Agulhas Leakage (AL), which was revealed by the simulated velocity field, was proposed to be a contributor to the associated freshening of AAIW. Further calculation showed that such a decrease could account for approximately 53 % of the observed freshening (mean salinity reduction of about 0.012 over the AAIW layer). The estimated variability of AL was inferred from a weakening of wind stress over the South Indian Ocean since the beginning of the 2000s, which would facilitate freshwater input from the source region. The mechanical analysis of wind data here was qualitative, but it is contended that this study would be helpful to validate and test predictably coupled sea–air model simulations.